THE FIVE HUMAN SENSES AS BATIK MOTIFS FOR CASUAL CLOTHING - Arif Riyan Fauzi; Guntur (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
The five human senses are a physiological system in the human body which has the function of recognizing, feeling and receiving various physical stimuli. The Five Senses are unique and contain many values in them. The aim of this final assignment is to be able to describe and be able to create.which can later be developed into the creation of written batik motifs. The exploration stage is the first stage by directly observing the human senses which will then lead to the design stage of alternative designs which will later be selected and used as motifs and designs for clothing.casual.Embodiment, is the final stage, where this stage begins with making patterns, scratching, batiking, coloring, locking colors, sagging, and sewing until finishing. The process of creating this work uses dabbing techniques and uses tools and materials such as wax, canting, stove, remasol dye, primisima cloth, and brocade cloth. The results of the creation of this work are 5 casual clothes with different titles and meanings for each dress, namely the work 1 with the title Grana, work 2 with the title Sesanti, work 3 with the title Tutur, work 4 with the title Gegaran, and work 5 with the title Senguhan. This design produces an innovation to inform the human senses and also batik art in the fieldfashion. Keywords: Human Five Senses, Batik, Clothing, Casual